Enhancement of Solubility BCS Class II and IV Pharmaceuticals by Liqusolid Technique: A review - Dwi Retno Sari; Yoga Windhu Wardhana; Taofik Rusdiana (Universitas Padjadjaran (Unpad), 2020)
Many techniques can be used to improve drug solubility, which is the development of the liquisolid technique. This technique has a mechanism for increasing the surface area of the drug as well as wetting from the addition of non-volatile solvents resulting in a lower surface tension and contact angle, so the solubility and drug release very increases. Liquisolid tablets show a lower contact angle compared to the conventional tablets. The liquisolid technique approach is also promising because the process is simple in making low production costs and allows the manufacturing industry, including non-volatile solvents, fillers, dryers, and disintegrants. Liquisolid characterized by specific instruments such as powder x-ray diffraction (PXRD), Fourier transforms infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and scanning electron microscope (SEM). Several liquisolid techniques are described in this review. The liquisolid technique is proven and able to change the physicochemical properties of active pharmaceutical ingredients, especially the solubility, drug release, and stability of the formula so that this technique can be a solution for class II and IV BCS pharmaceutical active drug classes.Keywords: Active Pharmaceutical Ingredients, Contact Angle, Solubility, Drug Release, Stability, Liquisolid Technique